2014
DOI: 10.1111/trf.12597
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of adverse reaction rates for PAS C versus plasma platelet units

Abstract: PAS C PLTs were statistically superior and noninferior to PPs with respect to the transfusion-related AR rate. PAS C noninferiority and superiority were also demonstrated for ATRs and FNHTRs, separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 28 publications
3
72
0
Order By: Relevance
“…The correlation between ABO antibody titer levels and age of donors has been previously described . Our results suggest that a strategy reducing the number of group O PLT donations from females under 30 years old may also reduce the risk of hemolysis from ABO‐incompatible plasma containing PLT transfusion, but this strategy may negatively impact the PLT donor pool already strained by TRALI mitigation strategies …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The correlation between ABO antibody titer levels and age of donors has been previously described . Our results suggest that a strategy reducing the number of group O PLT donations from females under 30 years old may also reduce the risk of hemolysis from ABO‐incompatible plasma containing PLT transfusion, but this strategy may negatively impact the PLT donor pool already strained by TRALI mitigation strategies …”
Section: Discussionsupporting
confidence: 71%
“…PLT AS (PAS) for use with PLT has recently gained US Federal Drug Administration approval and is reported as mitigating allergic transfusion reactions. Thus PAS can be considered as another mitigation strategy against hemolysis due to high‐titer ABO antibody . Importantly, in vivo PLT count recovery evaluated by corrected count increments measured 12 hours posttransfusion is not significantly changed compared to increments measured with PLTs stored in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent hemovigilance studies have also reported that the use of riboflavin and UV light–treated PLTs has the potential to reduce the frequency of transfusion reactions, specifically febrile and allergic reactions . It is known that PLTs suspended in an additive solution are associated with less allergic and febrile transfusion reactions than PLTs stored in 100% plasma . Such reactions can also be prevented by the use of riboflavin and UV light to inactivate WBCs not removed by leukoreduction and thus avoid cytokine release by WBCs.…”
Section: Discussionmentioning
confidence: 99%
“…For febrile reactions, they showed no difference between platelets in plasma and in PAS, with an incidence of 0.70 and 0.59%, respectively. For transfusion reactions in general, Cohn et al [25] reported an incidence of 1.37% for platelets in plasma, versus 0.55% for platelets in PAS-C, giving a relative risk of 0.403 with an upper confidence limit of 0.663. Allergic reactions were the most frequent, with a rate of 0.29% for platelets in PAS-C versus 0.82% for platelets in plasma.…”
Section: Transfusion Reactionsmentioning
confidence: 99%